The development of orally administrable gemcitabine prodrugs with D-enantiomer amino acids: Enhanced membrane permeability and enzymatic stability - Tsume, Yasuhiro (Eur J Pharm Biopharm, 2013)
Gemcitabine prodrugs with D- and L-configuration amino acids were synthesized and their chemical stability in buffers, resistance to glycosidic bond metabolism, enzymatic activation, permeability in Caco-2 cells and mouse intestinal membrane, anti-proliferation activity in cancer cell were determined and compared to that of parent drug, gemcitabine. Prodrugs containing D-configuration amino acids were enzymatically more stable than ones with L-configuration amino acids. The activation of all gemcitabine prodrugs was 1.3–17.6-fold faster in cancer cell homogenate than their hydrolysis in buffer, suggesting enzymatic action. The enzymatic activation of amino acid monoester prodrugs containing D-configuration amino acids in cell homogenates was 2.2–10.9-fold slower than one of amino acid monoester prodrugs with L-configuration amino acids. All prodrugs exhibited enhanced resistance to glycosidic bond metabolism by thymidine phosphorylase compared to parent gemcitabine. Gemcitabine prodrugs showed superior the effective permeability in mouse jejunum to gemcitabine. More importantly, the high plasma concentration of D-amino acid gemcitabine prodrugs was observed more than one of L-amino acid gem-citabine prodrugs. In general, the 5′-mono-amino acid monoester gemcitabine prodrugs exhibited higher permeability and uptake than their parent drug, gemcitabine. Cell proliferation assays in AsPC-1 pancreatic ductal cell line indicated that gemcitabine prodrugs were more potent than their parent drug, gemcitabine. The transport and enzymatic profiles of 5′-D-valyl-gemcitabine and 5′-D-phenylalanyl-gem-citabine suggest their potential for increased oral uptake and delayed enzymatic bioconversion as well as enhanced uptake and cytotoxic activity in cancer cells, would facilitate the development of oral dosage form for anti-cancer agents and, hence, improve the quality of life for the cancer patients.